Rancang Bangun “Siwani” Media Pembelajaran Perakitan Komputer Di Masa Covid 19 - Yosi Nur Kholisho; Siti Nurwaniza; Kholida Ismatulloh (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
Currently the world is facing a big problem, namely the emergence of corona virus disease (covid-19), the entry of this virus inhibits all human activities, including in the field of education. Based on interviews with teachers of computer subjects and basic networks, the subject of computer assembly in the learning process is still hampered by time when learning theory during the Covid-19 period, the application of current learning is using whatsapp groups, where the teacher provides material files and assignments. Online learning with this whatsapp group is considered less than optimal from both teachers and students resulting in students having difficulty understanding the material, based on these problems a solution is given by developing learning media with the name "SIWANI". The objectives of this research are: 1) to build SIWANI as a learning media for computer assembly; 2) determine the feasibility of SIWANI as a learning media for computer assembly; 3) knowing students' responses to SIWANI as a learning media for computer assembly. The method used is Research and Development (R&D) with the ADDIE development model. The results showed that the material expert feasibility test obtained an average of 85% with a very feasible category. While the feasibility test by media experts obtained an average percentage of 81% with a very feasible category. While student responses obtained an average percentage of 83% with a very high category.